Current status of wastewater treatment through large-scale treatment wetlands in the State of Veracruz, Mexico - Martínez-Aguilar, Karina Elizabeth; Marín-Muñiz, José Luis; Álvarez-Hernández, Luis Manuel; Delfín-Portela, Elizabeth; Zamora-Castro, Sergio A. (Renewable Energy, Biomass & Sustainability, 2024)
The use of treatment wetlands has increased globally in the last twenty years. In the State of Veracruz, Mexico, CONAGUA has only registered six wetland-based treatment plants. However, recent research has revealed the existence of additional wetland treatment systems in operation that were not listed in the CONAGUA inventory. The main objective of this study is to diagnose the current situation of wastewater treatment in the State of Veracruz, Mexico, and identify the large-scale treatment wetlands that exist in the region. The study will focus on the design and implementation characteristics of these wetlands. The research is qualitative and descriptive, based on publications between 2000 and 2023 from Google Scholar and databases published by CONAGUA. The information review process used a content analysis technique to identify the geographical location of the wetlands, their installation area, the type of wetland, the type and volume of treated water, the vegetation used, and the year of installation. The results identified 12 large-scale treatment wetlands currently in operation in the State of Veracruz, Mexico, which have different design characteristics. The main variations are in the type of plants used. Some of these wetlands have been in operation for periods ranging from 1 to 17 years, but there is no updated information regarding their current functioning. Thus, future research is suggested to focus on the situational diagnosis of these systems years after their installation.